Exosome-mediated microglia-astrocyte interactions drive neuroinflammation in Parkinson's disease with Peli1 as a potential therapeutic target - Min Guo; Ao Guan; Minjie Zhang; Haiqing Li; Weishi Liu; Bangsheng Wu; Weiwei Shen; Tongyao You; Suzhen Liang; Qiang Dong; Jintai Yu; Yanxin Zhao; et al. (Pharmacological Research)
Neuroinflammation is a key feature of Parkinson's disease (PD), characterized by activated microglia and the conversion of astrocytes into the neurotoxic phenotype, exacerbating the neuroinflammation. In PD, microglia critically drive neurotoxic reactive astrocytes (A1, A1-like, or neuroinflammatory reactive astrocytes)—though the underlying mechanisms remain elusive. Given the established role of exosomes as critical intercellular messengers, we investigated whether microglia-derived exosomes contribute to neurotoxic astrocyte transformation. Our findings demonstrate that microglial depletion via PLX3397 significantly attenuated α-synuclein pre-formed fibrils (α-syn PFF)-induced neurotoxic reactive astrocytes. Crucially, purified microglial exosomes alone proved sufficient to drive astrocyte polarization toward the neurotoxic phenotype in mice. Complementary approaches—exosome depletion from microglial supernatants and GW4869-mediated exosome secretion blockade—convergently alleviated neurotoxic astrocytic phenotype conversion, verifying exosome-dependent mechanisms. Mechanistically, PFF-activated microglial exosomes carried proinflammatory factors and toxic α-syn oligomers. These cargo components exacerbated neuroinflammation through induction of the neurotoxic astrocyte phenotype and direct mediation of neuronal damage. Critically, upon intrastriatal injection, these exosomes were internalized by astrocytes in the striatum and substantia nigra, triggering concurrent astrocyte proliferation and neurotoxic phenotypic conversion. Additionally, we identify Peli1, an E3 ubiquitin ligase selectively enriched in microglia, as a key regulator of microglia activation and exosome release. Peli1 inhibition alleviates microglia activation and neurotoxic astrocyte conversion. Moreover, our findings reveal a feedback loop between neurotoxic astrocytes and microglia, wherein neurotoxic astrocytes upregulate Peli1 expression in microglia, further promoting neuroinflammation. This study highlights microglial exosomes in regulating neurotoxic astrocyte activation and identifies Peli1 as a novel target for PD intervention.